Anaphylaxis shock with laryngeal edema: a case report - Pranata, Anak A. N. S.; Wulandari, Dewi C.; Setiawathi, Ni P.; Suryana, Ketut (International Journal of Advances in Medicine, 2024)
Anaphylaxis is a serious systemic or hypersensitivity reaction that rapid in onset and affect airway, breathing, and/or circulatory problems, and that is usually associated with skin and mucosal changes. Laryngeal edema is observed in 40-50% of death cases. A 49-year-old Asian female came to emergency department with chief complaint of difficulty to breath since 30 minutes ago after took cefixime and also common cold drug (Combination of paracetamol, glyceryl guaifenesin, phenylephrine, and Chlorpheniramine maleate). She also complained difficulty to speak and feeling strangulated on her neck. She ever had an allergic reaction, when she was child after suffering fever and common cold, but didn’t remember the name of the medication. History of food allergies was denied. On physical examination revealed, dyspnea and minimal tachycardia. Present of laryngeal edema, on auscultation stridor and wheezing on both lungs. Diagnosis of anaphylactic shock was made, and immediately giving epinephrin and followed by corticosteroid and antihistamine. The signs and symptoms of anaphylaxis might differ from patient to patient and impact the skin, gastrointestinal tract, respiratory system, and heart. Anaphylaxis fatal cases rise when laryngeal edema and cardiovascular organ involvement occur. The most frequent triggers are produced by food, venom from insects, and prescription drugs. The risk of death in anaphylaxis patients is decreased with prompt treatment. It is necessary to assess and maintain breathing, circulation, and airways in addition to determining the cause. Anaphylaxis can be potentially lethal or life-threatening, thus prompt identification and appropriate treatment are necessary.